Study of Convection using the Kain-Fritsch Convective Scheme of WRF Numerical Model - L. , Jambajamts; M. , Tsoozol; Kh. , Tsookhuu (Scientific transaction of the National University of Mongolia. Physics, 2022)
We have studied a convection from a convective cloud that brought damage to people and economy on 14-15 July of 2010 in the area of Ulaanbaatar city, using ARW, the third version of the WRF simulation program. The results have been compared to meteorological observed data and the reliability was 87%.